Kesiapan Industri Rumah Tangga Mebel terhadap Penerapan Sistem Verifikasi Legalitas Kayu di Yogyakarta - Reza Ahda Sabiila; Eko Ruddy Cahyadi; Hartrisari Hardjomidjojo (Jurnal Manajemen dan Organisasi, 2018)
Illegal logging and illegal timber trade have been ones of major causes of deforestation in many countries, including Indonesia. Indonesian Timber Legality Assurance System (Sistem Verifikasi Legalitas Kayu/SVLK) is an instrument to improve governance of timber sector. The system ensures the legality of timber harvested, transported, processed, and marketed by Indonesian forestry enterprises. Implementation of SVLK is mandatory. Since implemented, SVLK has increased export of forest products. However, the export is dominated by large scale enterprises. On other hand, many of small and medium scale industries are yet registered. According to background and issues, the study aims to analyze distribution network, small business profit, cost of SVLK implementation, and the application of svlk feasibility financial simulation on small scale industries furniture. Primary data collection was carried out with purposive sampling method through deep interview and questionnaires. The result showed there were 3 alternative distribution channels of community wood marketing in Yogyakarta. Each distribution channel has different characteristics. Cost percentage of SVLK implementation is 4.00%. The actual challenge is in the equally distributed information and incompatibility between the requirements of SVLK and the life of small scale industries. SVLK requires Rp 7.787.500,- in early periode and Rp 6.230.000,- to be paid every 2 years. The total cost is Rp 32.707.500,- for 10 years. There are only 7% of small scale industries knowing about SVLK. Small scale industries which don’t know clearly is 50 %, while other small scale industries claim to be uninformed. Based on the study, NPV Rp 10.011.212,-, BCR 1,13 dan investment return rate 18%. Feasibility financial simulation showed SVLK implementation is possible, although has little positive sales development. Small scale furniture industries with 144 m3 raw material per year usage have to target 12% sales development in first year. In second year of implementation, small scale furniture industries cashflow has negative point. It caused by surveillance cost. Small scale furniture industries interest to SVLK implementation was in minimum point. Small scale furniture industries interest to SVLK implementation can be increased by certification financing programs and the export market assurance.